Participação social e cooperação internacional descentralizada: a experiência de Belo Horizonte em projetos da Rede Mercocidades - Castro, Helton Reis de (2015)
After the worldwide changes in the political field starting from the second half of the twentieth century, participatory and deliberative democracy has been consolidated from the 1990s in the Brazilian socio-political scenario. Developments in the field of democratic deepening theories, or radical democracy, bring approaches that improve representative democracy involving the institutions providing, at the same time, greater performance space for civil society and local governments. In the same period, the world experienced the process of globalization with limited scope and emphasis on trade aspects, which came to be questioned by local governments, traditionally relegated to the back burner in the field of public policies, integration processes and international relations. Claiming for greater scope for action, eleven South American cities created the Mercocidades Network, an association of municipalities which covers the territory of MERCOSUL in search for affirmation of the leading role of local governments in public policy scenes. Through coordinated action in network and decentralized international cooperation actions, the city of Belo Horizonte actively incorporated in this process participating in projects promoted by Mercocidades: Laboratório de Políticas Locais, Inovação e Coesão Social and Comunic@ Escola MERCOSUL in recent years. It has become the focus of this research that seeks to contribute to the understanding of the networking articulated action by local governments in perspective of strengthening social actors, aiming at the development of public policies with participatory approach while laying on relevance the role of cities in this process in another proposal for regional integration with social inclusion.